Analisis Penggunaan Similes dan Metaphors pada Novel Berjudul “Hard Time” sebagai Tulisan Deskriptif - Lilik Damayanti (Pusat Penelitian dan Pengabdian kepada Masyarakat Politeknik Negeri Balikpapan., 2019)
Figurative language is a way to engage readers and deliver them through writing in a more creative form. The two categories of figurative languages that are most widely known are similes and metaphors. The purpose of this study was to analyze the use of similes and metaphors contained in a literary work in the form of a novel entitled